Pemberdayaan Kelompok Masyarakat Desa Karya Pandai Besi Kampung Dokdak Melalui Penggunaan Mesin Belt Grinder Untuk Meningkatkan Kualitas Barang Produksi - Suryana, Aan; Darna, Nana; Nugraha, Awaludin (Unri Conference Series: Community Engagement, 2024)
The Dokdak Village blacksmith community group is a community whose majority livelihood is as blacksmith craftsmen with a total of 27 craftsmen. This community group is located in Baregbeg village, Ciamis district. The Blacksmith Village community group has quite a lot of problems, one of which is the use of traditional means of producing goods. This causes the low quality of the goods produced, so they are still unable to compete with those produced outside the Ciamis district area. To overcome this problem, it is necessary to use modern goods production equipment, namely belt grinder machines to improve the quality of the goods produced. The method used in this service activity is Participatory Rural Appraisal (PRA) with the steps taken, namely socialization, training, application of technology, mentoring, and evaluation as well as program sustainability activities after the service is completed. The results of service activities show that community knowledge and understanding regarding the use of belt grinder machines increased from 50% to 80%. Apart from that, the use of a belt grinder machine can improve the quality of the goods produced, increasing the selling value of goods that were initially sold for IDR 50,000 to IDR 150,000. Based on the explanation above, it can be concluded that the use of modern goods production tools can help solve the problems faced by craftsmen.